Study of competency level of students, teachers and mentors based on the integrated approaches of contemplative education, coaching system, and research - et. al., Kannika Bhiromrat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The production of competency-based teachers according to the Bachelor of Education program can apply the concept of contemplative education, coaching and research as the bases in guiding the teaching student production process by integrating with learning management in courses and training in educational institutes for students. The objective of this research is to study the competency level of students, teachers and mentors according to the integrated approaches of contemplative education, coaching system, and research. The sample groups used in this research were 1) 9 early childhood education teachers, 2) 30 second year students of early childhood education program in the academic year 2020, 3) 7 kindergarten mentors in the early childhood development center. The specific method of selection was employed. The research instruments consisted of 1) the CCR comprehension assessment, 2) the teacher qualification evaluation form, 3) the CCR coaching competency evaluation form and, 4) the learning management competency evaluation form. The statistics used for data analysis were mean and standard deviation. The findings were; 1) the capacity of teaching qualifications of the supervisors, mentors, and students was at the highest level, 2) the capacity of knowledge in learning management based on the CCR approaches of the supervisors, mentors, and students was at the highest level, 3) the CCR coaching capacity of the supervisors and mentors was at the highest level, 4) the student’s CCR learning management was at the highest level..